Digital Environment For Sinusoidal Vibration Test Control Of An Ac Power Source-fed Electrodynamic Shaker - Flora, Leandro Della; Gründling, Hilton Abílio (Eletrônica de Potência, 2006)
This paper presents a digital environment for sinusoidal vibration test control of an AC power source-fed electrodynamic shaker. The proposed solution is based on a high performance switching-mode inverter with digital control obtained by means of a PC compatible platform. An interactive user interface software developed in the microcomputer offers an easy and automated execution of fixed frequency, swept sinusoidal, resonant search or personalized tests over a very wide frequency and test load mass range. The design considerations of the switching-mode power amplifier, modeling of the electrodynamic shaker, features of the control platform and the acceleration measuring system as well as experimental results are described in detail.